Expanding the limits of nephron‐sparing surgery: Surgical technique and mid‐term outcomes of purely off‐clamp robotic partial nephrectomy for totally endophytic renal tumors. (1st January 2022) - Tuderti, Gabriele; Brassetti, Aldo; Mastroianni, Riccardo; Misuraca, Leonardo; Bove, Alfredo; Anceschi, Umberto; Ferriero, Mariaconsiglia; Guaglianone, Salvatore; Gallucci, Michele; Simone, Giuseppe
Abstract : Objectives: To report surgical technique, perioperative, oncological, and mid‐term functional outcomes in a single‐center purely off‐clamp robotic partial nephrectomy series for totally endophytic masses. Methods: A retrospective analysis of a prospectively collected, institutional review board‐approved renal cancer database was carried out to include patients with a totally endophytic renal tumor treated with off‐clamp robotic partial nephrectomy between January 2013 and December 2020 at our center. Our database was queried to identify cases that had been assigned 3 points for the "E" domain of the R.E.N.A.L. nephrometry score and 3 points for the "exophytic rate" domain of the PADUA (Preoperative Aspects and Dimensions Used for an Anatomical) nephrometry score. Preoperative indocyanine green renal mass marking was performed in 33 patients, in whom the tumor was vascularized by a specific feeding artery. Surgical steps, perioperative, oncological and functional data were reported. Results: Fifty‐six consecutive patients with totally endophytic renal masses were treated. The median tumor diameter was 3 cm, and median PADUA and R.E.N.A.L. scores were both 10. The median operative time was 82 min. Low‐grade Clavien complications occurred in two patients (3.6%) and high‐grade Clavien complications were observed in four patients (7.1%). Positive surgical margins were detected in one patient; 2‐year recurrence‐free, cancer‐specific, and overall survival rates were 100%, 100%, and 98.2%, respectively. At a median follow‐up of 24 months, new onset of chronic kidney disease stage 3b occurred in one patient. At last follow‐up, the median estimated glomerular filtration rate was 77 mL/min, with a median estimated glomerular filtration rate percent decrease of 5.5%. Trifecta was achieved in 91% of patients. Conclusions: Purely off‐clamp robotic partial nephrectomy is a feasible and safe surgical approach, even in totally endophytic renal tumors, providing a favorable perioperative complications rate, excellent oncological outcomes, and negligible impact on renal function at mid‐term follow‐up. Indocyanine green preoperative marking of endophytic renal tumors represents a useful tool for rapid intraoperative identification of the mass, real‐time control of resection margins, and a more precise dissection.